FEDERAL INCOME TAX PRACTICE IN THE UNIFORM CERTIFIED PUBLIC ACCOUNTANT EXAMINATION. - Bower, James B. (The Accounting Review, 1955)
This article focuses on federal income tax practice in the uniform certified public accounting (CPA) examination. The uniform CPA examination has had a major role in establishing and maintaining today's high standards. The purpose of the examination is to determine the technical qualifications of young men and women to enter the field of public accounting. If the uniform examination is analyzed through the years, the development of a dynamic profession will unfold through the evaluation of the technical information required of candidates. There are many interesting relation- ships connected with the rapid expansion of accountancy as a profession. One of the more interesting is to note that the expansion of the profession occurred in the period when Federal income taxes were influencing an increasing number of business decisions and claiming a substantial portion of business profit. The CPA is a qualified tax practitioner to the public, and no distinction is made between the tax specialist and the general practitioner. Professionally, this is probably an ideal situation, however, as in the case of accountants and attorneys alike, it could have its disadvantages if all practitioners were not qualified in income tax matters or were not aware of their own limitations and responsibilities.